Fatores associados ao não conhecimento da política nacional de humanização – PNH - SILVA, Rutiely Tomaz (2019)
To create integrality and quality in Health attention, an assistance model elaborated to create hearing methods of users and health professionals needs to be communicated. In this perspective and according to SUS’s (Brazilian Health Care Public System) principles, the Ministry of Public Health created in 2003 the Nacional Humanization Policy (PNH in Portuguese). This research has as general aim analyses the knowledge of the users about the guideline “Users Rights Defense”, part of PNH, in a high complexity hospital. The specific aims was: describe the users of Triagulo Mineiro Federal University Hospital (HC-UFTM), according to sociodemographic and health variables; identify items of the Users Rights Defense known by the users, verify the relations between sociodemographic and health variables with the lack of knowledge about the Users Rights Defense Guideline by the users. It is an quantitative study, with observational and transversal aspects, made at HC-UFTM with 182 hospitalized patients at the unit cares, that stayed at the hospital for 72 hours or more. The data collection was made by interview, with a data collection instrument created by the research authors with bibliographic basis turned to the PNH. Considering the patients interviewed, most were female (51,6%), at age over the 40’s (51,6%), that have studied between 4 and 8 years (59,9%) and individual income of 1 minimum salary (45,6%). Prevalence patients of Medical Clinic (33,5%) and Chirurgic Clinic (33%) and the period of hospitalization was from 3 to 5 days (61%). The most part of people interview (93,4%) are unaware about the PNH. 53,3% are aware about have rights and duties assured by the law; 96,7% never had access to the Rights and Duties of the Public Health System Letter. About receive information about their health conditions in a concise way, 96,2% answer that Yes, about their diagnosis; 98,4% about the kind of tests requested; 99,5% about the results of the testes requested and 93,4% about the period of hospitalization forecast. 66,5% answer that were asked if their family or caregivers should be informed about their health condition; 97,8% received guidance and information about the period after being discharged of the hospital; 100% answer that had not being discriminated by age, race, color or sexual orientation. 100% answer that the professionals used badges or other ways that identify them properly and 99,5% are satisfied with the health care services received at the hospital. The male (p=0,035); the age range over 40’s (p=0,010); the income of 0 minimum salary (p=0,047); those who claims not know that have rights and duties assured by the lay (p=0,046) were associated to the non-knowledge about the PNH. Considering the expose, it’s clear that despite being unaware about the PNH, the users experiences it in the hospital daily routine.